The employee’s perception of psychological safety: construct dimensions, scale development and validation - Canghong Wang; Yuwen Ning (BMC Psychology)
Abstract Although organisations can effectively resist risks and enhance organisational performance by creating a Perception of Psychological Safety (PPS) climate, there is a lack of PPS scales developed under a multidimensional integrated interaction perspective. Based on a review of relevant theories, this paper clearly defines the concept of PPS and proposes a three-dimensional model of PPS, including organisational- level PPS, team- level PPS, and dyadic- level PPS. In this paper, we develop and validate a scale for measuring PPS in the workplace using 12 startups in a relatively economically developed region in the southeastern coastal region of China as the empirical target. The results of the empirical analyses show that the scale we developed has a good level of reliability and consistency, as well as good content validity, convergent validity, and discriminant validity.